Protecting Intellectual Property Rights in the Digital Revolution: Ministry of Law's Role Reviewed - Manurung, Oktavia Pitta Marito; Simamora, Janpatar (Indonesian Journal Publisher, 2025)
Intellectual property rights violations are increasingly common in the digital age, resulting from the growth of digital content media. Low public awareness about the risks of access to illegal content is a major factor in intellectual property violations such as data theft, online trading of counterfeit goods. To solve this problem, the government and the general public must proactively increase law enforcement and educate the public on the importance of respecting intellectual property rights. The way digital technology protects intellectual property rights (IPR), has changed due to easier distribution and access to content on online platforms. Copyright infringement is on the rise, making current laws more difficult to enforce. This research aims to identify how the development of digital technology impacts copyright protection and to find the main problems faced by the Ministry of Law in enforcing the law against copyright infringement in the digital world. This research uses the normative juridical method, by analyzing legislation and conducting a literature review. The results of the analysis show that although digital technology provides people with new opportunities to build and spread work, it also poses problems for supervision and enforcement. To protect copyright in the digital age, the government and society need to take strategic actions to strengthen the legal framework and improve law enforcement capabilities to protect copyright. This is due to regulations that have not fully adjusted to the rapid changes in the digital world, as well as low public awareness of the importance of copyright protection.